Effect of Alpha Lipoic Acid on in vitro Maturation of Porcine Oocytes and Subsequent Embryonic Development after Parthenogenetic Activation - Young-Hun Kang; Sang-Hwan Hyun (The Korean Society of Animal Reproduction and Biotechnology, 2017)
Alpha lipoic acid (ALA) is a biological membranes compound. As the antioxidant, it decreases the oxidized forms of other antioxidant substances such as vitamin C, vitamin E, and glutathione (GSH). To examine the effect of ALA on the in vitro maturation (IVM) of porcine oocytes, we investigated intracellular GSH and reactive oxygen species (ROS) levels, and subsequent embryonic development after parthenogenetic activation (PA). Intracellular GSH levels in oocytes treated with 50uM ALA increased significantly (P < 0.05) and exhibited a significant (P < 0.05) decrease in intracellular ROS levels compared with the control group. Oocytes matured with 50 uM of ALA during IVM displayed significantly higher cleavage rates (67.8% vs. 83.4%, respectively), and higher blastocyst formation rates and total cell number of blastocysts after PA (31.6%, 58.49 vs. 46.8%, 68.58, respectively) than the control group. In conclusion, these results suggest that treatment with ALA during IVM improves the cytoplasmic maturation of porcine oocytes by increasing the intracellular GSH levels, thereby decreasing the intracellular ROS levels and subsequent embryonic developmental potential of PA.